2003
DOI: 10.2174/1381612033455099
|View full text |Cite
|
Sign up to set email alerts
|

Matrix Metalloproteinases: A Therapeutic Target in Cardiovascular Disease

Abstract: Cardiovascular disease is the leading cause of death in Western society. Extracellular matrix turnover is important in many cardiovascular pathologies, such as arterial remodeling, plaque rupture, restenosis, aneurysm formation and heart failure. Matrix metalloproteinases (MMPs) belong to a group of zinc and calcium dependent proteases and cause breakdown of the extracellular matrix. MMP inhibitors have been developed and tested for their effect on the outcome of oncological disease [1]. Recent preclinical res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
36
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(37 citation statements)
references
References 0 publications
0
36
0
1
Order By: Relevance
“…Proteinases from the MMP system participate in the proliferation and migration of SMC, and in matrix remodeling during arterial wound healing [3, [13][14][15][16][17]. Only MMP-2 appears to be expressed in the quiescent SMC, whereas expression of MMP-3, -7, -9, -12 and -13 is induced in injured, transplanted, or atherosclerotic arteries [18][19][20][21][22][23].…”
Section: Expression Of Mmp Componentsmentioning
confidence: 99%
“…Proteinases from the MMP system participate in the proliferation and migration of SMC, and in matrix remodeling during arterial wound healing [3, [13][14][15][16][17]. Only MMP-2 appears to be expressed in the quiescent SMC, whereas expression of MMP-3, -7, -9, -12 and -13 is induced in injured, transplanted, or atherosclerotic arteries [18][19][20][21][22][23].…”
Section: Expression Of Mmp Componentsmentioning
confidence: 99%
“…heart failure; fibrosis; mitochondria; sarcomere THE PAST DECADE HAS WITNESSED an increasing interest in the interactions of cardiomyocytes with the extracellular matrix, particularly with regard to the development of cardiac failure and fibrosis. Modulation of the cardiac extracellular matrix by various members of the large matrix metalloproteinase (MMP) gene family has provided important mechanistic insights into the evolution of left ventricular failure in the setting of both ischemic and nonischemic disease (10,11,20,29,49,51). The MMP gene family includes Ͼ20 discrete members, including the interstitial collagenases (e.g., MMP-1 and -13), the gelatinases (MMP-2, -9), and membrane-associated enzymes, including membrane type 1(MT1)-MMP (60).…”
mentioning
confidence: 99%
“…Scientific interest in metalloproteinases (MMPs) and their inhibitors has grown rapidly in the last few years, especially since it has been postulated that they could be relevant targets for treating atherothrombotic cardiovascular disease. 1 Some data suggest that circulating MMPs levels are elevated in patients with acute myocardial infarction (AMI), unstable angina, and also after coronary angioplasty. 2 Other studies showed that there is an increase of MMP concentration in macrophages, endothelium fibrous cap and vascular smooth muscle cells in the atherosclerotic plaque and some MMPs and tissue inhibitors of metalloproteinases (TIMPs) appear to be elevated more in patients with AMI and unstable angina than in healthy people.…”
mentioning
confidence: 99%